Aggressive adenomatoid odontogenic tumor of mandible showing root resorption: A histological case report - Ramandeep Saluja; Gurkiran Kaur; Preetinder Singh (Wolters Kluwer Medknow Publications, 2013)
Adenomatoid odontogenic tumor (AOT) is a benign odontogenic tumor with slow but progressive growth. The three variants: Follicular, extra follicular (both central type), and peripheral present with identical histologic findings. This case report describes a patient with a large AOT in the mandible of the extra follicular type which is the less common of the two central types. It also strikes as an unusual case as it shows significant root resorption of the involved displaced teeth which is not generally reported in AOT's.